Mental Disorder and Criminal Law - Stephen J. Morse (2011)
Mental disorder among criminal defendants affects every stage of the criminal justice process, from investigational issues to competence to be executed. As in all other areas of mental health law, at least some people with mental disorders, are treated specially. The underlying thesis of this Article is that people with mental disorder should, as far as is practicable and consistent with justice, be treated just like everyone else. In some areas, the law is relatively sensible and just. In others, too often the opposite is true and the laws sweep too broadly. I believe, however, that special rules to deal with at least some people with mental disorder are justified because they substantially lack rational capacity. Treating people with mental disorder specially is a two-edged sword. Failing to do so when it is appropriate is unjust, but the opposite is demeaning, stigmatizing, and paternalistic. The central normative question is when special treatment is justified. This Article will focus mainly on United States Supreme Court cases to review the current state of the law, with special attention to the contexts in which preventive detention is an issue. It makes no pretense to covering every issue, to providing a complete analysis of these cases, or to comprehensive coverage of all the arguments concerning the issues raised. The Court’s cases are simply a vehicle for organizing the overview. The goal is to explore what I consider the most just approach in each area. In some cases, my preferences are foreclosed by constitutional constraints; in others, the preferred approach could be achieved by statute or by state supreme court decisions